REVIT ALISASI UMKM (Usaha Mikro, Kecil, dan Menengah) DALAM RANGKA PENGEMBANGAN KEK (Kawasan Ekonomi Khusus). (Micro, Small and Medium Entreprises Revitalization in the Framework of Special Economic Zone Development ) - Bisri, Slamet Riyadi (MAJALAH ILMIAH GEMA, 2010)
Micro, Small and Medium Enterprises have very significant roles in Indone-sian economy nevertheless their r oles ar e in informal sector which shows thatther e is an informalisation of economy . The workfor ce can not benefited from theformal sector . W ith the existence of the Law number 39 year 2009 on SpecialEconomic Zone (SEZ) there will be major economic development in the selectedr egions, which means an economic development.The incentives of SEZ in the directed regions by the Coordinating Ministerof Economics namely : North Coast of Java Island, East Coast of Sumatra Is-land, the Islands of Kalimantan and the Island of Sulawesi ar e signs of economicgrowth in the regions. The foreign investors as well as business players definitelywill take the advantage of SEZ in Indonesia. “Will the MSME take the advantageof the future development?” It is still in questions. There is a set of criteria forSEZ and some of them require that the region hinterland is also ready with thehuman resources, MSMEs, and local industrial companies as well as a conduciveenvironmental for development.The government of the selected SEZ should also preparing the human re-sources as many as possible to support the coming modern industrial activities,otherwise in order to fulfill the needs the companies might recruits the manpowerfr om abroad with the suitable competencies. The MSMEs should grab the oppor-tunities thr ough increasing the competencies as man power suppliers, servicesproviders as well as vendors in any activities which would be needed by the SEZ’ sindustries. If this could happen the SEZ would benefit the MSME and in turnwould benefit the Indonesian economy in a more synergistic endeavor . The Indo-nesian Government and the other stakeholders have roles to play .Key W ord : Revitalisasi, Micro, Small and Medium Entreprises